SEJARAH ISLAM DAN POLITIK DI PAKISTAN - Adib Abbiya Qowiyyudin; Moh. Azmi Fauzi (Program Studi Sejarah Peradaban Islam Institut Agama Islam Darullughah Wadda'wah, 2023)
This research aims to explain the history of Islam and politics in Pakistan. This type of research is descriptive using a qualitative approach. The main sources for this research are books and literature on the history of Islam and political policies in Pakistan. The source analysis process begins by reviewing data obtained from various sources or information. Data collected through documentation and literature study after being read, studied and then analyzed. Next, analyze the text of the document used as a reference in the research, so that keywords and flow are found that explain what is behind a political policy phenomenon. So that in accordance with the objectives to be achieved in this research, the analysis method used is qualitative using relevant sources for the analysis process. Political dynamics in Pakistan are quite high because there were upheavals, crises and military coups that often occurred in the first few years of its formation and in the following years. The incompetence of leaders in managing government has resulted in riots in various regions and ever-changing political movements. During the leadership of Ali Butto, the government system was changed from Islamic to secular, resulting in people being disappointed with Butto's leadership and ending in a military coup. In the subsequent dynamics of Zia Ul-Haq's government, there was development of all aspects of life which could improve government and change to an Islamic ideological system.